Eksekusi Jaminan Fidusia dalam Keadilan Hukum Investasi Bagi Kreditur Dan Debitur - Pujana, I Dewa Gede Saputra Valentino; Anis , Friend Henry; Setlight , Mercy (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2023)
Fiduciary givers are individuals or corporations who own objects that are objects of fiduciary guarantees. The purpose of this study is to analyze and describe how legal justice invests for creditors in relation to the execution of fiduciary guarantees. The research method using normative juridical research is also supported by primary data, namely the data comes from interviews. The approaches used in discussing this research are statutory, conceptual, comparative, and interview approaches. The results of the study show that with the constitutional court decision number 18/puu-xvii/2019 regarding the object of fiduciary guarantees, initially there must be agreement from both parties so that justice can be achieved as in the considerations of the constitutional court. There needs to be a mechanism for delaying debt payment obligations that must be applied in the settlement of bad loans by debtors submitted by each local court if the debtor in good faith can still continue the vehicle loan so that the execution of fiduciary guarantees by creditors does not occur to the detriment of the debtor